TAâLÃL AL-AHKÃM DARI MASA RASULULLAH HINGGA MASA ULAMA USHÃL - Musyafaah, Nur Lailatul (Al-Jinayah: Jurnal Hukum Pidana Islam, 2016)
Abstract: TaâlÃ®l al-ahkÃ¢m is explaining by finding the legal reason.Â  At the time of the Prophet, taâlÃ®l was contained in the Qurâan and hadith, among them: 1.â Illat was embodied with the character of law, 2. Stating the legal position with its reason and historical background, 3. Explaining command accompanied by tafdhÃ®l, 4. Explaining law with its reason marked with the letter of taâlÃ®l, 5. Explaining law and its explanation about the benefit or in otherwise. The methods of taâlÃ®l al-ahkÃ¢m at the time of companion: 1. Elimination of the penalty for refusing mafsadah, 2. Law is changed because its legal reason hasÂ  been lost. 3. Not carrying out the command of Allah and His Messenger for the reason of mafsadah if the work is still performed, 4. Assigning the unassigned law at the time of Prophet for the sake of refusing mafsadah, 5. Doing something which was not done at the time of the Prophet for the reason of gaining benefit, 6. EstablishingÂ  law based on the text without searching the illah. The methods of taâlÃ®l al-ahkÃ¢m at the period of tÃ¢biâÃ®n and tÃ¢biâ tÃ¢biâÃ®n: 1. Advancing benefit, the law contained in the textis absolute or contrary to the public welfare, 2. Using the method of maslahah mursalah. 3. Leaving a permissible act by the reason of mafsadah. The methods of taâlÃ®l al-ahkÃ¢m in the period of Muslim scholars of ushÃ»l: with text, ijmÃ¢â, and al-sabr wa al-taqsÃ®m.Keywords: TaâlÃ®l al-ahkÃ¢m, period of the Messenger, period of the Muslim scholars of ushÃ»l.Â Abstrak: TaâlÃ®l al-ahkÃ¢mÂ adalah menjelaskan danÂ caraÂ menemukan ilat hukum. Pada masa Rasulullah, taâlÃ®l terdapat pada al-Qurâan dan hadis,Â di antaranya; 1. Ilat menyatu dengan sifat hukum, 2. Menyebutkan hukum beserta sebabnya. 3. Menjelaskan perintah diiringi dengan lafadzÂ tafdhÃ®l, 4. Menjelaskan hukum beserta ilatnya yang ditandai dengan hurufÂ taâlÃ®l,Â 5. Menjelaskan hukum disertai dengan penjelasan maslahatnya, atau sebaliknya. MetodeÂ taâlÃ®l al-ahkÃ¢mÂ pada masa Sahabat: 1. Meniadakan hukuman karena alasan menolak mafsadah, 2. Hukum menjadi berubah, karena ilatnya telah hilang, 3. Tidak melaksanakanÂ perintah Allah dan RasulNya, karena adanya mafsadah apabila pekerjaan tersebut tetap dilaksanakan. 4. Menetapkan hukum yang belum ditetapkan Rasulullah demi menolak mafsadah, 5. Mengerjakan pekerjaan yang tidak dikerjakan pada masa Rasulullah, dengan alasan kebaikan, 6.Â Menetapkan hukum berdasarkan nas yang ada tanpa mencari ilat hukum.MetodeÂ taâlÃ®l al-ahkÃ¢mÂ pada masa TÃ¢biâÃ®n dan TÃ¢biâ TÃ¢biâÃ®n: 1. Mendahuluan maslahat, jika hukum yang terkandung dalam nas bersifat mutlak atau umum bertentangan dengan kemaslahatan, 2. MenggunakanÂ metode maslahah mursalah. 3. Meninggalkan pekerjaan yang mubah atau sunnah, karena jika dikerjakan akan mendatangkan mafsadah.Â MetodeÂ taâlÃ®l al-ahkÃ¢mÂ pada Masa Ulama UshÃ»l: Dengan nash, ijmaâ, dan al-sabr wa al-taqsÃ®m.Kata Kunci:Â TaâlÃ®l al-ahkÃ¢m, Masa Rasulullah, masa Ulama UshÃ»l.Â